Enhancing ESL learners’ writing through collaborative learning with canva - Asiah, Kassim; Noraisah Nurul Fatwa, Mohd Razali (Penerbit UMPSA, 2024)
In response to the unrest caused by the intrusion of the COVID-19 pandemic, which has impacted educational and collaborative environments, this study investigates the role of Canva as a technological tool in enhancing collaborative writing among engineering students. The research employs a pre-test and post-test design, with participants assigned to experimental and control groups to evaluate Canva’s impact on writing performance and user perceptions. Using paired samples t-tests and inferential statistics, the study finds a significant positive relationship between students' perceptions of Canva’s ease of use and their performance in collaborative writing tasks. The finding suggests that learners who utilise Canva in their collaborative writing tasks perform better than those who do not. Qualitative analysis indicates that Canva effectively promotes creativity, improves collaboration, and boosts engagement and writing quality in language learning activities. Despite its benefits, the study identifies challenges, including the initial learning curve and dependency on Internet connectivity, which must be addressed to maximise Canva's effectiveness in educational settings. The study concludes that Canva holds significant potential for enhancing collaborative writing and recommends further research to explore its long-term benefits and overcome existing limitations.